Rehabilitation of People with a Brain Injury Through the Lens of Networked Learning: Identity Formation in Distributed Virtual Environments - Konnerup, Ulla; Castro Rojas, Maria Dolores; Bygholm, Ann (Proceedings of the International Conference on Networked Learning, 2016)
This paper will demonstrate how avatar-mediated interactions and learning in networks might lead to identity formation and rehabilitation of language after a brain injury. With references to Vygotsky's notion of the social origins of higher mental functions (1978) and Hutchins claims that cognition is something that is embodied and externally distributed. (Hutchins, 1995), we will discuss identity formation after a brain injury in relation to Networked Learning (NL). The discussion is based on data from the first author's research (Konnerup, 2015) on avatar-mediated rehabilitation of people with aphasia (PWA). Rehabilitation is conceived as a collaborative endeavour, conducted in a social virtual community with peer-to-peer interactions. Central is the comprehension that relearning language is embodied and related to social interactions and renegotiation of identity. Individuals who lose the ability to communicate find it difficult to re-tell their own story and are at risk of being marginalised (Duchan, Linda, Garcia, Lyon, & Simmons-Mackie, 2001; Shadden & Agan, 2004). Although the focus in aphasia intervention has shifted from relearning correct language to a greater emphasis on life participation and regaining feelings of belonging to society and family, there is still a need for concrete suggestions for approaches that provide new contexts within which identity formation can be renegotiated. In recent years, learning via online social networks has been recognised as a means of constructing learning and identities through participative interactions. Additionally, avatar-mediated activities in games, online communities, and E-learning have become a part of everyday play, communication, and learning. As these methods are still in their infancy, reflections on traditional forms of learning, teaching and rehabilitation, are needed. Teachers and/or speech therapists need a deeper understanding of these methods, and to become skilled in practicing technology-mediated teaching. We will discuss the positions that rehabilitation in online communities and NL share; how insights from NL pedagogy can inform the development of rehabilitation; and, conversely, how our finding add perspectives to NL. In doing so, we will introduce the concept of locale framework, and how a specific setting and embodied interactions might trigger autobiographical memory, relearning communication competencies and renegotiation of identity.